ANALYSIS OF THE THINKING PROCESS OF ELEMENTARY SCHOOL STUDENTS INPRES 1 KAWATUNA IN SOLVING AKM PROBLEMS BASED ON WALLAS THEORY IN TERMS OF LEARNING STYLES - Riska, Riska; Mubarik, Mubarik; Sukayasa, Sukayasa; Mallo, Bakri (Prima: Jurnal Pendidikan Matematika, 2025)
This study aims to describe students' thinking process in solving Minimum Competency Assessment (AKM) questions based on learning styles. This research uses a descriptive qualitative approach with the method of analyzing the thinking process according to Wallas which includes four stages, namely: the preparation stage, the incubation stage, the illumination stage, and the verification stage. The research subjects consisted of three students, namely one student with a visual learning style, one student with an auditory learning style and one student with a kinesthetic learning style. The data collection technique was carried out through giving a learning style questionnaire, giving AKM test questions and unstructured interviews, after which it was analyzed using the data condensation model, data presentation, and conclusion drawing/verification. The results showed that in the preparation stage, subjects with visual, auditory and kinesthetic learning styles gathered information by reading the questions repeatedly. At the incubation stage, subjects with visual, auditory and kinesthetic learning styles understand the problem well then reflect on ideas to solve the problem. At the illumination stage, visual, auditory and kinesthetic subjects find ideas and express ideas to solve the problem, but at this stage auditory and kinesthetic subjects cannot find more than one idea while visual subjects can find more than one idea to solve the problem. At the verification stage, visual, auditory and kinesthetic subjects express their ideas verbally well, but at this stage auditory subjects do not re-examine the answers they have done while visual and kinesthetic subjects always re-examine the answers they have done.